2008
DOI: 10.1021/jp8051906
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Interaction between Nanoparticles and Membranes: Hydrophobic/Hydrophilic Effect

Abstract: Understanding the interactions of nanoparticles (NPs) with biological system, especially interactions with cell membranes, is critical for the rational design of nanocarrier agents and drug delivery systems. Here, we have performed coarse-grained molecular dynamics simulations aimed at the effect of hydrophilic/hydrophobic properties of nanoparticles on the interaction with cell membranes (dipalmitoylphosphatidylcholine or DPPC bilayer). Two kinds of nanoparticles (hydrophobic and semihydrophilic) are modeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(191 citation statements)
references
References 39 publications
9
174
0
8
Order By: Relevance
“…Thus, it seems that the NP-SLB interaction is mainly driven by the high surface energy of the bare NPs that tend to extract lipids from the bilayer. 16,57 Montis and co-workers 58 Although the HC constitutes the most permanent protein shell on the NP surface and it is considered the biological identity of the NP, a soft corona is also associated in vivo to the NPs and its role in the bio-nano-interaction is still elusive. For this reason, experiments with pure serum and NPs in serum were performed, to investigate if weakly associated and free proteins have a role in the NP-SLB interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it seems that the NP-SLB interaction is mainly driven by the high surface energy of the bare NPs that tend to extract lipids from the bilayer. 16,57 Montis and co-workers 58 Although the HC constitutes the most permanent protein shell on the NP surface and it is considered the biological identity of the NP, a soft corona is also associated in vivo to the NPs and its role in the bio-nano-interaction is still elusive. For this reason, experiments with pure serum and NPs in serum were performed, to investigate if weakly associated and free proteins have a role in the NP-SLB interaction.…”
Section: Discussionmentioning
confidence: 99%
“…5 NPs can adhere to the lipid bilayer and cause changes in the lipid phase, 7 induce formation of lipid domains [8][9] or pores and extract lipids 10 inducing lipid bilayer disruption. [11][12] Physical chemical properties of NPs, 5,13 such as size, 4,11,[14][15] charge 12,16 and surface chemistry [17][18][19][20] are the main factors modulating NP-membrane interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation base on the free energy in this study showed that the size of nanoparticles affects the translocation time differently, suggesting that the size has significant impacts on its translocation across the lipid bilayer [40]. Results of coarse-grained molecular dynamics simulations indicated that a hydrophobic nanoparticle can result in the inclusion into the DPPC bilayer, whereas a semihydrophilic nanoparticle is only found to adsorb into the membrane because of the potential substantial energy barrier of particle wrapping, implicating that the endocytosis-like mechanism is an energy-mediated process [41]. Thermodynamics of charged nanoparticle adsorption on charge-neutral membranes was also simulated [42].…”
Section: Cellular Uptake and Processingmentioning
confidence: 99%
“…Both experimental studies and computer simulations indicated that cationic AuNMs induce more disruption of the cell membrane than anionic AuNMs [68,69], as it depends on the charge density. For the hydrophobic interactions, a simulation study showed that hydrophobic NMs (diameter: 10 nm) could be embedded into the cell membrane, whereas semihydrophilic NMs only adhered to the membrane [70]. 11mer capto1undecanesulfonate AuNPs that only had hydrophilic sulfonate ligands were endocy tosed by cells, whereas the 66-34 1octanethiol AuNPs (AuNPs coated with a 2:1 molar mix ture of 11mercapto1undecanesulfonate and 1octanethiol) with a hydrophilic-hydrophobic striated ligand shell directly penetrated the cell membrane owing to ligand rearrangement [57].…”
Section: Future Science Groupmentioning
confidence: 99%
“…For example, Gu et al simulated the effect of the hydro phobic property of NMs and the effect of charges on NM-biomembrane systems [70,91]. Hydrophobic interaction and electrostatic attraction improved the interaction process.…”
Section: Mathematical and Numerical Modeling Approaches For Nm-biomembrmentioning
confidence: 99%